Going for Smart Growth : Making Research and Innovation Work for Bulgaria - World Bank (Washington, DC, 2013)
This policy note provides a detailed assessment of Bulgaria's innovative capacity and offers policy recommendations to increase the impact of science and innovation. Part one of the policy note provides an assessment of Bulgaria's innovation capacity in the public and private spheres. Specifically, the note examines: (i) recent trends in Bulgaria's export performance, benchmarking Bulgaria relative to comparator countries; (ii) the characteristics of innovation activities in Bulgaria's private sector, as seen by enterprise surveys; (iii) developments in technological invention and scientific production, by analyzing the statistics about patents granted in the US Patent and Trademark Office (USPTO) and the European Patent Office (EPO) as well as data on scientific publications. Part two provides recommendations that could facilitate the implementation of the NRP and the Scientific Research Strategy, including sectoral analysis to guide innovation policy in priority industries. The recommendations are divided into the following areas: (i) attaining the 1.5 percent Research and Development, or R&D and Gross Domestic Product, or GDP target under the Europe 2020 strategy; (ii) strengthening the institutional and policy framework for research and innovation; (iii) achieving better results from national funding instruments, the National Innovation Fund and the National Science Fund; (iv) increasing absorption of European Union (EU) funds targeting innovation; and (v) developing targeted innovation policies and instruments for priority sectors.